Rutas de la expedición. "La piedra en el zapato expedicionario" - Ortiz de Acosta, Rosalba; Beltrán Rojas, Mercedes; Rondón de Herrera, Gloria; Mejía Parra, Ximena; Piñeros, Nancy; Yepes, Angela; Palacios Campillo., Zavil; Contreras, Maria; Coral, Karol; Navas de López, Myrian (Nodos y Nudos, 2001)
NA